(untitled) (GESTIÓN Y TENDENCIAS, 2019)
In order to confront the globalization of markets and the need for financial accounting information for the various parties interested in company information, prepared on the basis of a common accounting language, the need arose to implement the International Financial Reporting Standards. That process, not free of difficulties and hesitations, entailed a significant change and challenge for accounting and auditing professionals (professionals of information and control), as well as for the universities that train them, given their responsibility to supply the market with professionals up to date in these standards for their professional practice.